2003
DOI: 10.1159/000068921
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Proliferative Responses following Sepsis in Neonatal Rats

Abstract: Both experimental and clinical evidence suggest a suppression of T-cell function in burn and sepsis. The objective of the present study was to evaluate splenocyte and purified T-cell proliferative response and IL-2 production in septic neonatal rats. We also examined if alterations in T-cell proliferation and IL-2 production in neonatal sepsis is due to elevation in PGE2. PGE2 is known to play a significant role in T-cell suppression during sepsis in adults. Sepsis was induced in 15-day-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…It appears that in this model treatment with resveratrol impacts on prostanoid production in the lung; this result agrees with similar in vitro results described by Dallal and colleagues (44). Although studies have been published showing resveratrol to inhibit COX-1 and COX-2 gene expression in vitro (18,19), the results of this experiment suggest that the reduction in PGE 2 levels was not due to an impact on gene expression of either of these enzymes involved in the production in prostanoids.…”
Section: Discussionsupporting
confidence: 92%
“…It appears that in this model treatment with resveratrol impacts on prostanoid production in the lung; this result agrees with similar in vitro results described by Dallal and colleagues (44). Although studies have been published showing resveratrol to inhibit COX-1 and COX-2 gene expression in vitro (18,19), the results of this experiment suggest that the reduction in PGE 2 levels was not due to an impact on gene expression of either of these enzymes involved in the production in prostanoids.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies of the effects of non‐selective COX inhibition during sepsis have been conducted with the intent of determining whether COX inhibition is beneficial and safe. Available data indicate that COX inhibitors are generally safe and may ameliorate several clinical and immunological parameters 46,48–50 . However, treatment with COX inhibitors did not appear to improve the rate of survival in patients with sepsis even though it has been shown to ameliorate the extent of IL‐12 reduction and to provide survival advantage in septic animals 45,51 , 52 …”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that NS-398 exhibited protective effects in two models of sepsis characterized by infection in the setting of trauma-induced immunosuppression, whereas the drug was largely ineffective when sepsis was induced in immunocompetent animals. Dallal and coworkers [30] demonstrated that T-cell suppression during neonatal sepsis is accompanied by a decrease in IL-2 production. Such suppression was ameliorated by COX-2 inhibitor, suggesting a role for PGE 2 in suppressed T-cell-mediated immune function in neonatal sepsis.…”
Section: Discussionmentioning
confidence: 99%